Lectotypification of Dioscorea vexans (Dioscoreaceae), an endemic and rare species from Andaman and Nicobar Islands, India - Pagare, Ravikiran S.; Wilson, Arisdason; Sellappan, Krishnan; Janarthanam, Malapati K. (Phytotaxa, 2015)
Dioscorea Linnaeus (1753: 1032) is represented by ca. 616 species worldwide (eMonocot, 2015). Prain & Burkill (1936, 1938) reported ca. 50 species from India, while Karthikeyan et al. (1989) in their ‘Florae Indicae Enumeratio: Monocotyledonae’ listed 30 species and 27 varieties. However, only 29 species and 2 varieties have been recognized now as the number of accepted taxa from India (eMonocot, 2015). During the course of herbarium consultation as part of a taxonomic study of the genus Dioscorea in the northern Western Ghats, we came across type specimens of Dioscorea vexans Prain & Burkill (1908: 456), housed at CAL, and also images of some of the type specimens in the Herbarium Catalogue, Kew (http://specimens.kew.org/herbarium/K000098220; K000098221 and K000098222). As no holotype was indicated by the authors in the protologue, and no lectotype has since been designated, the specimens are considered syntypes, and thus the name has to be lectotypified in accordance with Article 9.2 of the Melbourne Code (McNeill et al. 2012). The lectotype has been selected among the existing syntypes, and designated here for D. vexans.